Knowledge regarding subfertility among reproductive age women in selected VDC of Baglung District - Shrestha, Ruksana; Shrestha, Kopila (Journal of Chitwan Medical College, 2018)
Introduction: The infertile couples experience stress in relationships with family and friends. They cut off themselves from other as they are uncomfortable to share it and they consider subfertility a private problem. Knowledge is a key factor associated with fertility self-care and initiation of the treatment when needed. The main objective of the study was to assess the Knowledge regarding Subfertility among Reproductive Age Women. Methods: A descriptive cross sectional research study was carried out to assess Knowledge regarding Subfertility among Reproductive Age Women in Baglung District. Non-probability purposive sampling technique was used to select the sample. Data were collected by using structured questionnaire through face to face interview. Obtained data were analyzed using descriptive statistics like mean, frequency, percentage and inferential statistics such as Chi-square test to find out association between knowledge and selected socio-demographic variables. Results: Findings of the study showed that majority of the respondents (72.2%) had inadequate knowledge, 25.0% had moderate knowledge and only 2.8% had adequate knowledge. There was significant association between knowledge and types of family at p=0.003. Conclusion: The findings highlighted lack of knowledge regarding subfertility in women. Thus, knowledge should be provided through mass media, different health campaign for the improvement of knowledge regarding subfertility among reproductive age women.